Effort to Get Reading Interest Through Parenting - Marti, Marti; Labibah, Labibah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
The influence of the family in developing an interest in reading is very large and very important. Families have the task of building a good reading culture, a culture that can condition families to be involved in good reading activities. Because reading can change each individual's perspective and direct their views outward. Through parental involvement, which is the main priority in developing interest in reading. Parental involvement is basically needed at all times for children at an early age, where at this age children begin to develop knowledge, attitudes, emotional morals and scharacter formation. Therefore, this research takes the title